Permanent pacemaker use after cardiac transplantation: completing the audit cycle. - Holt, N. D. (1996)
OBJECTIVE: To determine the effects of delaying permanent pacemaker implantation in cardiac transplant recipients from less than tree weeks to three weeks or more post transplantation-a change prompted by an earlier audit. DESIGN: Retrospective review of resting 12 lead electrocardiograms and prospective 24 hour ambulatory electrocardiograms. Comparison of pacemaker usage before (period 1) and after (period 2) the policy change in November 1990. SETTING: Outpatient department, supra-regional cardiopulmonary transplant unit. PATIENTS: All 30 consecutive orthotopic cardiac transplant recipients who received a permanent pacemaker within one month of transplantation between May 1985 and August 1995. MAIN OUTCOME MEASURES: Presence of pacing on the 12 lead electrocardiogram and during 24 hour ambulatory electro-cardiogram monitoring (pacemaker programmed to 50 beats per minute). RESULTS: 16/152 (10.5%) cardiac transplant recipients received permanent pacemakers in period 1 compared with 14/180 (7.8%) in period 2 (P = NS). Evidence of pacing was seen on 12 lead electrocardiograms at three months in 37.5% recipients in period 1 compared with 78.6% in period 2 (P = 0.03). At six months pacemaker usage had declined to 18.8% in period 1 and 35.7% in period 2 and at three years to 13.3% in period 1 and 40% in period 2 (P = NS for both). 21% patients in period 1 paced on ambulatory 24 hour monitoring compared with 38.5% in period 2 (P = NS). CONCLUSIONS: Delaying permanent pacemaker implantation to three weeks or more after cardiac transplantation reduced the proportion of permanent pacemaker implantations, slightly but not significantly. There was a significant increase in permanent pacemaker usage at three months post transplantation with trends towards increased usage at later times, suggesting more appropriate selection of patients for permanent pacing.